Effect of Ocimum sanctum Linn (Tulsi) on body weight and some biochemical parameters in restraint stressed albino rats - Siraji, Dilruba; Islam, Nadira; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2009)
Background: With the increased trend of urbanization of our society, the incidence of various stress related diseases are increasing day by day. People under chronic stress often tends to seek relief through drugs, which may have side effects. But some natural supplements called adaptogen, can be more beneficial in reducing symptoms of stress. Objective: The present animal model experimental study was designed to observe the effects of restraint stress on body weight, serum ALT, AST, Glucose, Cholesterol and their modifications by Ocimum sanctum Linn (tulsi) pretreatment which is an Ayurvedic adaptogen and has a long history of therapeutic use. Study design: For this purpose, 30 albino rats aged 90 to 120 days were included in this study. Twenty rats of experimental group were further subdivided into two groups. One group consisted of 10 rats exposed to one hour restraint stress daily for 7 days and 10 rats of the second group were pretreated with tulsi for 7 days before exposure to stress in the same way. 10 non stressed , non pretreated rats were taken into control group.This study was undertaken in the laboratory of the Department of Physiology,BSMMU during the period from July 2003 to June 2004. Methods: The body weight of all control rats were recorded daily in the morning. Body weight of the experimental rats were recorded just before exposure to stress. After completing the experiment , the animals were sacrificed and blood was collected . Serum glucose, cholesterol and ALT,ASTwere determined by standard laboratory technique. Data were compared among the groups and the results were statistically analyzed using unpaired student t' test. Results : The body weight in untreated stressed group was significantly lower (p < 0.001) than those of the control group and tulsi pretreated group. Serum levels of glucose, cholesterol, aminotrasferases (ALT and AST) were significantly higher (p < 0.001) in stressed group than those of control . Again in Tulsi treated group all these biochemical parameters were significantly lower (p < 0.001) than those of stressed group. This restraint stress-induced changes in body weight and biochemical parameters may be due to hypophagia, altered secretion of various metabolic hormones and neurotransmitters, changes in membrane permeability & hypovolaemia resulting from stress induced secretion of corticosterone and epinephrine through hypothalamo-pituitary adrenal axis activation. Conclusion: Prevention of stress induced changes in biochemical parameter by tulsi pre treatment indicates its anti stressor effect. Key words: Restraint stress; adaptogen;Ocimum sanctum Linn (tulsi); glucose; cholesterol; ALT; AST. Â  doi: 10.3329/jbsp.v3i0.1791 J Bangladesh Soc Physiol.2008 Dec;(3):29-34. Â 